A fotoautobiografia como espaço de recordação: fragmentos em álbuns de memória sobre a Universidade Federal da Paraíba no Arquivo Afonso Pereira - Gonçalves, Eveline Filgueiras (2016)
Like photography, the archival object is endowed with singularity and records the influences of time in the form of events. By its indexical nature, photography occupies a cultural role as a witness, which contributes to make it an object, by its very essence, archival. In this work, we analyze the educational dimension of Paraiba Afonso Pereira da Silva. For this we elaborate his fotoautobiografia, based on the photographs and albums contained in his private personal archive, focusing on his action as founding educator of the UFPB. We analyzed the photographic information of his photographic collection to describe the icons, indices and symbols depicted in the images and to produce the photoautobiography from the historical and social information contained in the photographs. We start from the hypothesis that the photoautobiography is a source of memorialistic information. In this sense, the Information Science is present by perceiving photography as a document, source of potential information capable of producing memory. Thus, we choose self-writing, not only because it has a qualitative character, but also because it is a practice that involves autobiographies. These practices of self-production lead us to understand a set of actions that were elaborated little by little by Afonso Pereira da Silva, from the most directly linked autobiographies to the creation of a memory of self, carried out with the collection of material objects . Starting from a reading of his deeds, we put them in dialogue with his own trajectory of educator, that composes the collection of the center of memory.